Manual de Procedimientos para el Programa de Residencias Estudiantiles en el área de Trabajo Social del Departamento de Vida Estudiantil y Servicios Académicos del Tecnológico de Costa Rica, Sede San Carlos - Bello-Cruz, Karen Dixiana (Instituto Tecnológico de Costa Rica, 2015)
This project shows the development of a Manual of Procedures for the Student Housing Program in the area of Social Work of the Department of Student Life and Academic Services (DEVESA) that aims at increasing the program's efficiency in managing their work. The project has a qualitative research approach and is characterized as a descriptive research. The media used for data collection were the survey and interview, and direct observation to a greater understanding of the implementation of the procedures. The analysis technique used in procedures was the Hexameter Quintilian. With the project it was found that certain procedures should be improved so that they can be performed in a more efficient manner within the program of student dorms. It is recommended that the proposed Procedures Manual Volume II is used with its recommendations for better management of the program.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2015.
Keywords: Residencias estudiantiles; Manual de procedimientos